2012
DOI: 10.1371/journal.pone.0039844
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Species in Putative Ancient Asexual Darwinulids (Crustacea, Ostracoda)

Abstract: BackgroundFully asexually reproducing taxa lack outcrossing. Hence, the classic Biological Species Concept cannot be applied.Methodology/Principal FindingsWe used DNA sequences from the mitochondrial COI gene and the nuclear ITS2 region to check species boundaries according to the evolutionary genetic (EG) species concept in five morphospecies in the putative ancient asexual ostracod genera, Penthesilenula and Darwinula, from different continents. We applied two methods for detecting cryptic species, namely th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 74 publications
1
44
0
4
Order By: Relevance
“…It can be argued that the on-going global warming could facilitate colonization of northern habitats by non-indigenous species coming mainly from Africa, through migratory birds stopping at the Iberian Peninsula in their routes. Among the most common ostracods in the studied reservoirs, we found D. stevensoni, a species with cosmopolitan distribution (Sohn, 1987;Karanovic, 2012), but see Schön et al (2012) for a discussion of Darwinulidae cryptic species. Despite we found a relative high number of species in the studied reservoirs, it must be noticed that about half of the samples did not contain living specimens.…”
Section: Discussionmentioning
confidence: 91%
“…It can be argued that the on-going global warming could facilitate colonization of northern habitats by non-indigenous species coming mainly from Africa, through migratory birds stopping at the Iberian Peninsula in their routes. Among the most common ostracods in the studied reservoirs, we found D. stevensoni, a species with cosmopolitan distribution (Sohn, 1987;Karanovic, 2012), but see Schön et al (2012) for a discussion of Darwinulidae cryptic species. Despite we found a relative high number of species in the studied reservoirs, it must be noticed that about half of the samples did not contain living specimens.…”
Section: Discussionmentioning
confidence: 91%
“…For example. Bode et al (2010) found close to 40 cryptic species in a single ostracod morphospecies Eucypris virens Jurine, 1820, while Schön et al (2012) identified several cryptic species in the putative ancient asexual darwinulid ostracods using molecular markers. Whereas previously several ostracod workers correctiy wamed for significant variability in valve morphology of ostracods as a consequence of different water chemistries (see, for example, Finston, 2000), present day research detects cryptic and discrete genetic clusters ('species') that are often unidentifiable based on morphology.…”
Section: Introductionmentioning
confidence: 95%
“…This method identifies discrete clusters in molecular phylogenies as "phylogenetic species", comparing the genetic distances within and between the clusters. This method has already been applied successfully to ostracod phylogenies, e.g., for Eucypris virens by Bode et al (2010), for Bennelongia by Martens et al (2012) and for darwinulids by Schön et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Eucypris virens (Jurine), close to 40 cryptic species have been described from Europe and North Africa (Bode et al 2010), while Schön et al (2012) found three cryptic species in Darwinula stevensoni (Brady & Robertson) and eight in Penthesilenula brasiliensis (Pinto & Kotzian). Analysis of DNA sequence data of Romecytheridea species of Lake Tanganyika, revealed a high cryptic diversity with allopatric distribution.…”
Section: A Single Variable Speciesmentioning
confidence: 96%